SUSTAINABLE DEVELOPMENT: REQUIREMENTS OF THE FUTURE ERA - Bala, Mukesh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Sustainable development is no longer a mere ideal or a set of abstract goals but has become an essential framework, for addressing the global challenges of the 21st century. As environmental, social, and economic systems are increasingly interconnected, the future of humanity hinges on our ability to achieve, sustainability across multiple dimensions. This paper reviews the evolving concept of sustainable development, its importance for the future era, and the key requirements for fostering it in a world marked by climate change, resource depletion, economic inequality, and technological, advancements. This review paper synthesizes insights from current literature, identifies the challenges ahead, and proposes the necessary steps for achieving sustainable development in the future.